Development and pilot testing of a metabolic syndrome intervention among market woman in Accra, Ghana - Achempim-Ansong, Gloria (My University, 2019)
Introduction: Metabolic syndrome (MetS) is considered to be a worldwide epidemic with high socioeconomic cost. MetS predisposes individuals to the risk of developing cardiovascular diseases, type 2 diabetes, stroke, and coronary artery disease. Studies have shown an increase in the prevalence of MetS among women globally and among Ghanaian women. Market work related factors such as physical inactivity and lack of proper nutrition due to preoccupation with trading activities, as well as lack of knowledge regarding the effect of this kind of work environment could predispose market women to the development of MetS. Even though various studies have been conducted on MetS, there is no evidence of a community-based intervention for improving health outcomes among market women in Ghana. Purpose of the study: The study sought to develop and pilot test a metabolic syndrome intervention aimed at improving the quality of life of market women with MetS as well as those at risk of the syndrome in Kaneshie Accra, Ghana. Research Methodology: The multi mixed method intervention design was used in the pre and post phases of this study. The study was implemented in three phases, made up of nine objectives. In Phase 1, the knowledge and prevalence of MetS, relationship among demographics, knowledge of MetS and MetS predictors, quality of life of the market women and the women’s opinion about practices that improve health were explored. Relationship among the QOL domains and MetS predictors was also established. An integrative literature review was also done to explore the MetS interventions employed by other researchers. Phase 2 comprised the development and expert review of a MetS intervention programme aimed at improving the health outcomes and quality of life of market women with MetS as well as those at risk of the syndrome. Phase 3 involved the pilot testing and evaluation of the health promotion programme. Results: Analysis of the total knowledge score of participants before the MetS intervention revealed that, only 68(19.5%) had adequate knowledge of MetS and therefore scored above 50%. A significant majority of 280 (80.5) scored below 50%. Secondly, 100(28.7%) out of the total sample of (n=348) tested positive for Metabolic Syndrome, per the IDF criteria. Again, 48.3% were identified to be at risk for developing metabolic syndrome while 23% tested negative. Results of a Tukey test conducted to compare the pre and post intervention knowledge and prevalence of MetS as well as the quality of life of the market women revealed that there was a significant improvement in participants’ knowledge, MetS parameters and quality of life after the MetS intervention programme. Conclusion: The results of the study indicate that a three-month physical activity, diet and health education programme for market women with MetS, contributed immensely in reducing the incidence of MetS, improving their knowledge of Mets as well as their quality of life. There is therefore the need for regular screening for Mets as well as awareness creation of the general public on MetS.
A thesis submitted to the faculity of health science, University of the Witwatersrand, in fulfillment of the requirement for the degree of Doctor of Philosophy Johannesburg, 2019
Keywords: Metabolic Syndrome; Women--South Africa; Exercise therapy